Farm input marketing in western Kenya : Challenges and opportunities - Chianu, Jonas N.; Mairura, Franklin S.; Ekise, IE (2008)
Widespread and increasing rural poverty in sub-Saharan Africa has been of great concern to development community. Low use of inputs by farmers, due to market constraints that reduce profitability of input use, is one of the factors responsible for the gap between potential and actual yields. Using questionnaire, this study interviewed 130 agro-input dealers in Kenya to analyze challenges and opportunities in input delivery. Results indicate that there has been a steady annual growth (2 – 22%, with mean of 16%) in their number. Di-ammonium phosphate fertilizer (stocked by 92% respondents) was most commonly stocked, followed by Calcium Ammonium Nitrate fertilizer (84%), Urea (78%), and NPK (40%). Other services provided by agro-dealers are input information (75% respondents), credit (13%), bulk breaking (8%), and spraying (4%). Inputs selling price increased with distance to markets; long distances to market disconnect villages from input supply chain. High transport cost (53%), low demand (30%), lack of market information (21%), lack of storage facilities (13%), and limited business knowledge (12%) were the most important constraints faced by agro-dealers. Policies and institutional frameworks suggested by dealers to streamline input trade were associated. The study concludes with suggestions on how to enhance efficiency of agro-dealers in input delivery.